To solve this system of equations, we can use the method of substitution or elimination.
Let's solve it using substitution:
First, solve the second equation for y:
-6x + y = 32
y = 6x + 32
Now, substitute this expression for y into the first equation:
4x - 8(6x + 32) = -36
4x - 48x - 256 = -36
-44x - 256 = -36
Add 256 to both sides:
-44x = 220
Divide by -44:
x = -5
Now that we have found the value of x, we can substitute it back into the second equation to find y:
-6(-5) + y = 32
30 + y = 32
y = 2
So, the solution to the system of equations is x = -5 and y = 2.
Solve the system of equations.
4x - 8y = -36
-6x + y = 32
1 answer